Effect of Convalescent Plasma Therapy on Viral Shedding and Survival in Patients With Coronavirus Disease 2019 - Zeng, Qing-Lei; Yu, Zu-Jiang; Gou, Jian-Jun; Li, Guang-Ming; Ma, Shu-Huan; Zhang, Guo-Fan; Xu, Jiang-Hai; Lin, Wan-Bao; Cui, Guang-Lin; Zhang, Min-Min; Li, Cheng; Wang, Ze-Shuai; et al. (The Journal of infectious diseases, 2020)
Abstract Currently, coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been reported in almost all countries globally. No effective therapy has been documented for COVID-19, and the role of convalescent plasma therapy is unknown. In the current study, 6 patients with COVID-19 and respiratory failure received convalescent plasma a median of 21.5 days after viral shedding was first detected, all tested negative for SARS-CoV-2 RNA within 3 days after infusion, and 5 eventually died. In conclusion, convalescent plasma treatment can end SARS-CoV-2 shedding but cannot reduce the mortality rate in critically ill patients with end-stage COVID-19, and treatment should be initiated earlier. Six patients with coronavirus 2019 disease and respiratory failure received convalescent plasma a median of 21.5 days after first detected viral shedding, all tested negative for severe acute respiratory syndrome coronavirus 2 within 3 days after infusion, and 5 eventually died.